Pemanfaatan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Based Learning (PBL) Terhadap Peningkatan Hasil Belajar Siswa pada Materi Sistem Ekskresi Manusia di MTsN Rukoh Kota Banda Aceh - Wahyu Rizki; Cut Nurmaliah; Muhammad Ali Sarong (Biotik, 2016)
This study aims to know study results through the use of students (LKPD) based the problem based learning to the matter excretory system.The research was carried out in MTsN Rukoh the city was Aceh in Maret-April 2016. Methods used in research is experimental methods to a draft pretest posttest control design. Study was conducted in the two namely VIII3 as a class experiment and VIII4 as a class control. An instrument used in this research using tests to appraise the outcome of student learning about double shaped choice. An analysis of data using the independent sample t-test with the help of spss 19.0 for windows on significant 0,05 standard .Test t show that t_count>t_table study results 7,137>2,002. Drawing conclusions utilization based LKPD based PBL can improve Student Achievement on the matter of excretion in MTsN Rukoh Banda Aceh.